2022
DOI: 10.1002/ctm2.1037
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle expansion of PMIS‐miR‐210 expression inhibits colorectal tumour growth via apoptosis and an XIST/NME1 regulatory mechanism

Abstract: Background Colorectal cancer (CRC) has a high mortality rate, and therapeutic approaches to treat these cancers are varied and depend on the metabolic state of the tumour. Profiles of CRC tumours have identified several biomarkers, including microRNAs. microRNA‐210 (miR‐210) levels are directly correlated with CRC survival. miR‐210 expression is higher in metastatic colon cancer cells versus non‐metastatic and normal colon epithelium. Therefore, efficient methods to inhibit miR‐210 expression in CRC may provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 91 publications
(233 reference statements)
0
6
0
Order By: Relevance
“…Therefore, the NME1 gene family exhibits multifunctionality, and its impact on metastatic progression may be contradictory in various cancers. Previous studies have found that the expression of NME1 is negatively correlated with metastatic potential in melanoma and epithelial tumors such as breast, liver, colon, and cervical cancer [3,[23][24][25][26] . However, in hematological malignancies such as ovarian and prostate cancer, the opposite relationship is observed, where upregulation of NM23-H1 is associated with poor prognosis [27,28] .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, the NME1 gene family exhibits multifunctionality, and its impact on metastatic progression may be contradictory in various cancers. Previous studies have found that the expression of NME1 is negatively correlated with metastatic potential in melanoma and epithelial tumors such as breast, liver, colon, and cervical cancer [3,[23][24][25][26] . However, in hematological malignancies such as ovarian and prostate cancer, the opposite relationship is observed, where upregulation of NM23-H1 is associated with poor prognosis [27,28] .…”
Section: Resultsmentioning
confidence: 96%
“…However, few studies have identified the functional connection between NME1 and genitourinary tumor development. Although NME1 has been shown to be upregulated in melanoma [25] , its detailed role and potential mechanisms in genitourinary tumors remain unclear and require further research. Our study revealed that amplification and mutations are the main mutation types of NME1, which can be observed in melanoma, infiltrating breast cancer, mesothelioma, pancreatic adenocarcinoma, and esophageal adenocarcinoma.…”
Section: Resultsmentioning
confidence: 99%
“…The PMIS-miR-200a transgenic mice have increased craniofacial bone volume and density and miR-200a regulates the osteogenic program (Hong et al 2021; Su et al 2022). We have shown that direct injection of highly purified plasmid DNA expressing a PMIS-miR construct into tissues resulted in efficient PMIS-miR expression (Eliason et al 2022). It is well known that cells will endocytose and express genes from highly purified naked plasmid DNA, which applies both in vivo and in vitro (Braun 2004; Wolff and Budker 2005).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 2 µg total RNA was used to generate complementary DNAs (cDNAs) using Takara Primescript for genes and Takara MirX for miRNAs. Quantitative real-time polymerase chain reaction (RT-qPCR) was performed as described previously (Eliason et al 2022). The cells were washed twice with phosphate-buffered saline (PBS) and then transfected with plasmid DNA (pDNA) encoding miR-200a at 5 μg/mL in serum-free medium (Opti-MEM; Life Technologies) with PEI for 18 h. EV was used as a control for nonspecific effects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation